Previewing distracters reduces their effective contrast - Allen, Harriet A.; Humphreys, Glyn W. (Elsevier, 2007)
In a visual search task, when half the distracters are presented earlier than the remainder (‘previewed’), observers find the target item more efficiently than when all the items are presented together—the preview benefit. We measured psychometric functions for contrast increments on Gabors that were presented as a valid preview for subsequent search, and when they were a non-predictive (dummy) preview. Sensitivity to contrast increments was lower (rightwards shift of the psychometric function) on valid, compared to dummy previews. This is consistent with an account of the preview benefit in terms of active inhibition, equivalent to lowering the contrast of previewed items that are being actively ignored.